Motivation within the power of humanity motivation of RCY Volunteers of PNRC-Iloilo Chapter - Bullo, Edron Jr. T. (2004)
This study attempts to find a relationship between motivation and voluntary service through the identification of the reasons why high school and college students join the RCY Program of the PNRC-Iloilo chapter, what makes them stay, the training courses and outreach activities they participate and undertake, and the benefits they gain from joining the said service organization.The study adopted the descriptive-case study approach of research. Twenty respondents/key informants were randomly selected from the various schools in Iloilo City, which have SRCY, and CRCY School Councils. The researcher made use of the primary data, gathered through the aid of guide questions on a Focus Group Discussion, and the secondary data derived from PNRC-Iloilo Chapter, the UPV Graduate Library, and the Internet for analysis and discussion. Findings show that motivation and voluntary service are relational. Both the High school and College students signified that they were motivated why they joined and decided to stay in the said organization as volunteers. Accordingly, they joined the RCY to be of service to relief operations. Other outreach activities include first aid services during parades and school activities, mall sales, sport activities, and other civic activities and celebrations held in the city and adjacent towns and RCY Summer Youth Camp. Volunteers are not financially remunerated but gains through the understanding and appreciation of humanitarian service, the knowledge they have learned in First aid and Basic Life Support, the value of responsibility, leadership and teamwork, the inculcation of moral values, and physical development. With these findings, the study advances to recommend that the PNR-Iloilo Chapter make use of their volunteers and work out for their development through trainings and activities, awads and recognitions to boost morale and dedication, and to booster fairness and fair play in the organization.
Research Paper (MM-Public Management). -- Iloilo City : UPV-CM, [n.d.].